Grain refinement by dynamic recrystallization during laser direct energy deposition of 316L stainless steel under thermal cycles. (April 2022) - Zou, Xi; Yan, Zhou; Zou, Ke; Liu, Wenyang; Song, Lijun; Li, Simeng; Cha, Limei
Abstract: During direct energy deposition (DED) process, the deposited material undergoes complex thermo-mechanical processing from subsequent thermal cycles. Dynamic recrystallization (DRX) can be activated under suitable strain and temperature conditions, which can induce grain refinement and homogenization. In this work, the evolution of temperature and thermal strain are experimentally measured, and the corresponding evolution of grain morphology, geometric dislocation density (GND), dislocation morphology and misorientation map under multiple thermal cycles during laser-DED of 316L stainless steel are investigated. Results show that DRX is activated during the 8th to 85th thermal cycles, during which temperature evolves in the range of 730 K – 800 K – 700 K and the corresponding strain evolves in the range of 4.5% – 7.0% – 5.3%. Nucleated grains grow by consuming grain boundary energy, with original columnar grains swallowed. Equiaxed grains are formed at the end of 90 thermal cycles. Dynamic recovery (DRV) would occur during the thermal cycling process, with the formation of sub-grains, the increased GNDs and the random grain misorientations through dislocation movement and entanglement promoted by high temperature and accumulated strain.